15 varsities vie to produce 'top entrepreneurs': Trade savvy: Simulation competition exposes students to the real processes of business world - Povera, Adib (New Straits Times, 2013)
TODAY is D-Day for 75 public university students competing in Universiti Utara Malaysia's National Business Simulation Competition for Public Institutions of Higher Learning. After a series of tasks, students from 15 universities will know which "entrepreneur" team has the wits and perseverance to come out tops.